A Review on Flood Events for Kelantan River Watershed in Malaysia for Last Decade (2001-2010) - Aminah Shakirah J.; Sidek L.M.; Hidayah B.; Nazirul M.Z.; Jajarmizadeh M.; Ros F.C.; Roseli Z.A. (Institute of Physics Publishing, 2023)
Rain; Water supply; Watersheds; Case-studies; Data and information; Heavy rainfall; Human health; Monsoon season; Precipitation areas; River watersheds; Tropical zones; Floods; agriculture; economic impact; flood; flood damage; flooding; information; monsoon; precipitation (climatology); public health; rainfall; tropical environment; urban area; vulnerability; water supply; watershed; Kelantan; Kelantan Basin; Malaysia; West Malaysia